Formation and Developmental Specification of the Odontogenic and Osteogenic Mesenchymes - Svandova, Eva; Peterkova, Renata; Matalova, Eva; Lesot, Herve (Frontiers in Cell and Developmental Biology, 2020)
Within the mandible, the odontogenic and osteogenic mesenchymes develop in a close proximity and form at about the same time. They both originate from the cranial neural crest. These two condensing ecto-mesenchymes are soon separated from each other by a very loose interstitial mesenchyme, whose cells do not express markers suggesting a neural crest origin. The two condensations give rise to mineralized tissues while the loose interstitial mesenchyme, remains as a soft tissue. This is crucial for proper anchorage of mammalian teeth. The situation in all three regions of the mesenchyme was compared with regard to cell heterogeneity. As the development progresses, the early phenotypic differences and the complexity in cell heterogeneity increases. The differences reported here and their evolution during development progressively specifies each of the three compartments. The aim of this review was to discuss the mechanisms underlying condensation in both the odontogenic and osteogenic compartments as well as the progressive differentiation of all three mesenchymes during development. Very early, they show physical and structural differences including cell density, shape and organization as well as the secretion of three distinct matrices, two of which will mineralize. Based on these data, this review highlights the consecutive differences in cell-cell and cell-matrix interactions, which support the cohesion as well as mechanosensing and mechanotransduction. These are involved in the conversion of mechanical energy into biochemical signals, cytoskeletal rearrangements cell differentiation, or collective cell behavior.